Implementasi Digital Marketing sebagai Stategi Pemasaran Industri Pariwisata Halal Perspektif Maqashid Syariah - Azizah, Siti Nur (Fakultas Syariah IAIN Kerinci, 2024)
In the era of globalization and rapid growth of the tourism industry, digital marketing in halal tourism has become a marketing strategy that is able to promote and increase the competitiveness of the halal tourism industry effectively, while remaining based on the principles of Maqashid Syariah. This research adopts a descriptive method with a qualitative approach, the data sources used mainly come from related journal articles and other literature relevant to the research topic. The results of the research confirm that digital marketing can be an effective means of promoting and developing the halal tourism industry which is in line with its objectives. Sharia, namely Maqashid Syariah. This research aims to provide insight into the implementation of digital marketing practices in the halal tourism industry in accordance with Maqashid Syariah principles. The aim is to provide business people, academics and policy makers with a deep understanding of the importance of promoting digital marketing by paying attention to Maqashid Syariah values in the era of digital technology.